Flow induced conformational transitions of macromolecules and their effect on chromatographic separations. (9th March 2015) - Kurganov, Alexander A.; Svec, Frantisek; Kanateva, Anastasiia Yu
Abstract: The conformation of macromolecules is significantly affected, both in free flow as well as when flowing in a confined space. These effects play a major role when passing polymer molecules in solution through a porous system such as chromatographic column or membrane. Current theories take into account the conformational changes of polymer molecules caused by flow, and provide a description of the unusual behavior of macromolecules during chromatographic separation. Due to the changes in conformation, the flow can also cause degradation of polymers which have a very large molar mass. Graphical abstract: